Pollen morphology in Brazilian species of Codonanthe (Mart.) Hanst. and Nematanthus Schrader (Gesneriaceae) - Gasparino, Eduardo Custodio; Da Cruz-Barros, Maria Amelia Vitorino; Chautems, Alain (Taylor & Francis, 2013)
Pollen morphology of 24 Brazilian species of Codonanthe and Nematanthus (Gesneriaceae) was investigated by means of light microscopy, scanning and transmission electron microscopy, in search of new characters that might contribute to taxonomic characterisation of the genera. The pollen grains are tricolpate or tricolporate, semitectate, reticulate, with simplicolumellate muri, sometimes with microreticulum and perforations, or duplicolumellate muri ring-shaped around lumina. The species studied were grouped into five pollen types on the basis of aperture characteristics and details of surface ornamentation. Sub-types were defined with reference to presence or absence of microreticulum and perforations around the lumina. Based on analysis of the morphology and measurements of pollen grains, we verified a close relationship among the genera, but can nevertheless discriminate their species. © 2013 Copyright Collegium Palynologicum Scandinavicum.
Keywords: Brazil; Episcieae; palynology; pollen grains